English Literature / A Survey for Students - Burgess Antony (Longman, 1978)
Foreword, What is Literature?, What is English Literature?, The First English Literature, The Coming of the Normads, Chaucer and After, Interlude - The English Bible, The Beginnings of Drama, The Beginnings of English Drama, Willian Shakespeare, Other Elizabethan Dramatists, Tudor Poetry and Prose, The age of Milton: End of a Period, The Age of Dryden, The New Drama, Poetry in the Age of Reason, Prose in the Age of Reason, The Romantics, The Victorian Age, Fresh Life in the Drama, The Coming of the Modern Age, To the Present Day, The British Novel Since 1950, English Verse Forms, Chronological Table, Suggestion for Further Reading, Index.
Foreword, What is Literature?, What is English Literature?, The First English Literature, The Coming of the Normads, Chaucer and After, Interlude - The English Bible, The Beginnings of Drama, The Beginnings of English Drama, Willian Shakespeare, Other Elizabethan Dramatists, Tudor Poetry and Prose, The age of Milton: End of a Period, The Age of Dryden, The New Drama, Poetry in the Age of Reason, Prose in the Age of Reason, The Romantics, The Victorian Age, Fresh Life in the Drama, The Coming of the Modern Age, To the Present Day, The British Novel Since 1950, English Verse Forms, Chronological Table, Suggestion for Further Reading, Index.